Pengembangan Kerangka Kerja TPACK pada Materi Koloid untuk Meningkatkan Aktivitas Pembelajaran dalam Mencapai HOTS Siswa - Dwi Kurnia Hayati; Sutrisno Sutrisno; Aprizal Lukman (Universitas Jambi, 2014)
Chemistry learning particularly colloid material has a scientific topic that measuring up to abstract and emphasizes the mastery of concepts until the microscopic level (molecular) symbolic. Thus, the implementation of learning need to be completed. Up till now, chemistry learning process is still dominantly conventional in teacher-centered, so that the students tend to be passive and less interested in learning. Therefore, it is necessary to develop an innovative learning to improve student’s learning activities, by integrating Technology, Pedagogy, and Content Knowledge (TPACK). Through the integration of TPACK, abstract material can be concrete with the use of simulation, as well as the learning will be student-centered learning by means of Inquiry Based Learning (IBL) model, so that students are more active in their learning and students’ Higher Order Thinking Skills (HOTS) will be achieved. The results indicating that learning activities at the meeting I 96.25%, meeting II 92.98%, meeting III 95.29%, and meeting IV 91.18% , all of them belong to the category of